Limbodessus skalei sp. nov., a new diving beetle species from the west Papuan Archipelago (Coleoptera: Dytiscidae, Bidessini) - Hendrich, Lars; Surbakti, Suriani; Balke, Michael (Zootaxa, 2020)
Here we describe Limbodessus skalei sp. nov. from the island of Waigeo, off the coast of West Papua. It can be easily distinguished from the nearby New Guinea mainland species as well as the other members of the genus by its small size and testaceous elytra with conspicuous darker broad basal and subapical patches. Altogether four Limbodessus species are now known from the New Guinea region.